Strategi Misi dalam Pelayanan di Bangsa-Bangsa - Immanuelia Deru; Minah Sarian; Anita Mariana Parulian Butar-Butar; Chanita Christie; Juanda Yulianus; Kezia Verena (Sekolah Tinggi Teologia Kerusso Indonesia, 2023)
Mission preaching aims to introduce Jesus Christ as the true God and the only human savior. Mission tasks should not be carried out by people who have positions as pastors, shepherds or leaders in a church or mission agency, but become the duty of all those who believe in Jesus Christ. The research method uses literature review to collect data in the form of books, articles related to the topic under study. The sources used were analyzed and then described using descriptive analysis methods arranged according to the research topic. The main points of study found are the importance of knowing and finding the right mission strategy, the need to apply spiritual warfare in evangelizing missions, and the need to know mission strategies to nations because God's message is to convey the gospel to the ends of the earth.